The Determinants of the Severity of State Fiscal Crises. (6th July 2016) - Mitchell, David T.; Stansel, Dean
Abstract : During the most recent recession, many state governments faced substantial budget shortfalls. Those shortfalls are often blamed on external factors like the declining economy or reductions in federal aid. What politicians themselves do, especially during expansionary years—whether they enact spending increases, implement tax cuts, increase the size of their rainy day funds, or some combination thereof—is typically given less attention. We examine those factors and find that fiscal stress tends to be positively associated with spending growth, negatively associated with the size of rainy day funds, and not statistically significantly associated with the unemployment rate or federal aid.